SEMANTIC AND LINGUOCULTURAL COMPARATIVE ANALYSIS OF EXPRESSIONS FORMED FROM ADJECTIVES EXPRESSING COLOR IN ENGLISH - Kholmatova Malika Ibadullayevna (Academia Science Repository, 2023)
This article is a section of lexicology devoted to the field of phraseology, in which phraseological units consisting of adjectives representing color in English and Uzbek linguistics are compared from a linguistic and cultural point of view, and the mentality, culture, and customs of a certain nation are analyzed. and valuable information about phraseological units that reflect their traditions.